Release kinetics of potassium from silica‐rich fern‐derived biochars. (14th April 2020) - Nguyen, Anh T. Q.; Bui, Tu A.; Mai, Nga T.; Tran, Hien T.; Tran, Son V.; Nguyen, Nam H.; Tsubota, Toshiki; Shinogi, Yoshiyuki; Dultz, Stefan; Nguyen, Minh N.
Abstract: Recently, low input agriculture has been encouraged because of its sustainability and environmentally friendly vision. Conversion of biomass into control‐released materials is one of the approaches to upcycle biomass and nutrients. This study aims at examining the dynamics of K release from Si‐rich biochars formed from various pyrolysis strategies with the findings expected to be applicable to develop new refinery strategies for biomass nutrients. A Si‐rich fern species [ Dicranopteris linearis (Burm.f.) Underw.] was selected to prepare biochars under various pyrolysis conditions (e.g., temperature, N2 supported). It was found that K was re‐located during pyrolysis and occurred as free K + ions, associated with organic matter and occluded in silica structure. Pyrolysis can be strategically applied to alter either the organic phase or the silica phase in the biochars in term of porosity and chemical reactivities, whereby controlling K release kinetics. The maximum level of released K was at 600 °C (5.4 g kg −1 ) which was about one order of magnitude higher than the minimum level of released K at 200 °C (0.55 g kg −1 ). This discrepancy in the release rates of K suggests that adjusting pyrolysis temperature can be a strategical practice to control K release and to develop biochar‐based K fertilizers.